Formation and Development of the Integrated Marketing Communications in the Activities of Production and Trade Enterprises - Dmitry V. Shkurkin; Irina N. Mayatskaya; Oksana V. Nikonova; Vladimir S. Novikov; Irina S. Vasilyeva; Svetlana G. Karepova (International Review of Management and Marketing, 2016)
Manufacturing companies in the Market Fast Moving Consumer Goods (FMCG) market characterized by new approaches to the elements of the distribution of products. Today, there was a change of the functional structure model of distribution of goods from the production company (producer) to the production and retail outlets (the mediator) to a trading company (intermediary), and to the end user. Appears multi-channel distribution with the addition of updated participants merchandisers and representatives of trade marketing, which allows you to maximize the efforts of manufacturing companies in the field of demand generation, promotion and positive image of the production company from trading company - then the consumer to use all the possibilities of contact with the consumer, and switching his preference to competing products on the goods and be an exemplary substitute product supplier. The authors of the technique of evaluating the cost-effectiveness of measures for the implementation of integrated marketing communications; lighted the issue of functioning of the integrated marketing communications of modern retail companies. With the author's position is considered the implementation of a new concept of integrated marketing communications.